The Role of Cultivation Systems in Quality Sugar Beet Production - Ungai, Kinga Diána; Győri, Zoltán (Acta Agraria Debreceniensis, 2005)
Producing sugar beet, as it is a demanding field crop, has contributed to the raising standard of plant production. It has an outstanding place among the plants that are cultivated in the intensive plant production system. Rentability of sugar manufacture is determined by the stability of yield and the quality (saccharose content) of sugar beet. In this way, the fundamental interest both of the producers and the processing industry is high yield and quality, year by year. The yield and the quality of the sugar beet are mainly determined by the plant production system, so we studied the effect of fertilization, irrigation and plant protection.